EVALUASI STABILITAS LERENG SPILLWAY BENDUNGAN BAGONG DAN EFEKTIVITAS PERKUATAN BORE PILE: ANALISIS PLAXIS LE DAN VERIFIKASI METODE ZENG - Christian Nova Rumayom; Kresno Wikan Sadono (Racic : Rab Construction Research, 2026)
The slope stability of the Bagong Dam spillway is controlled by colluvial soils and weathered volcanic rocks containing discontinuities that may form non-circular failure surfaces. This study assesses the existing slope condition and the effectiveness of bore-pile reinforcement using Limit Equilibrium analysis in PLAXIS LE. The lateral capacity of the piles is derived from rock-mass parameters obtained through the RMR–Hoek–Brown correlation and applied as lateral resistance in the numerical model. Independent verification is performed using the Zeng Method (2002) by computing translational equilibrium between slices. The results show that the factor of safety increases from 1.141 (existing) to 1.547 after installing bore piles. The Zeng Method yields FS = 1.5564, confirming strong agreement with the numerical model. The reinforcement enhances lateral resistance and shifts the critical slip surface deeper into more competent rock